Performance Test of Sieving Machine and Physical Characteristics of Corn Grits Production - Sutarsi Sutarsi; Ridwan Irianto (The University of Lampung, 2025)
Corn grits can be used as a substitute for rice as a staple food. This is based on the nutritional content of corn grits and also rice is a food ingredient that is dense in energy in its processing. Sieving is an important operating unit in addition to size reduction and cleaning which is intended to obtain a certain particle size in the manufacture of corn grits. The use of a sieving machine in selecting the size of corn grits determines the quality of the product. The size of corn grits also determines the level of public preference. The purpose of this study was to analyze the performance of the sieving machine and the physical quality characteristics of the resulting corn grits. The treatment variables of the study included the machine rotation speed (A) of 240, 320, 520 RPM and the sieving duration (B) of 10, 15, 20 minutes. Data analysis used ANOVA and DMRT Test. The combination of treatments (machine rotation speed and sieving duration) gave a significant difference to the sieving capacity. The treatment of rotation speed of 520 RPM and sieving duration of 20 minutes gave the largest sieving capacity of 94.66 kg/hour, sieving yield of 90%; water content of 13%, angle of repose of 0,62 radian (35,54ᵒ), and size distribution (D) of 1.78 mm. Keywords: Corn grits, Duration, Sieving performance, Physical characteristics, Rotation speed.